The Lived Experience of Racism in the Sikh Community - Brewer, Gayle (Journal of interpersonal violence, 2024)
The Sikh community may be more visible and vulnerable to racism than other religious groups, and previous research has documented the racism targeted at Sikh men and women in the United States. Relatively few studies have, however, addressed the racism experienced by Sikh communities in other countries, where racism may be less closely connected to the events of 9/11. The present study investigates the lived experience of racism in Sikh adults living in the United Kingdom. Six participants (5 male, 1 female) aged 19 to 30 years (M = 24.17, SD = 3.98) were recruited via advertisements placed on social media. Both Amritdhari Sikhs (n = 4) who had undertaken the Amrit Sanskar initiation ceremony or commitment and Sahajdhari Sikhs (n = 2) who had not undertaken the initiation participated. Semi-structured interviews were conducted (totaling 372 minutes of interview data), covering a range of subjects including personal experiences of racism and subsequent responses to the racist abuse. Interpretative Phenomenological Analysis of the interview transcripts identified five superordinate themes. These were (1) Appearance and Visibility; (2) Inevitability and Normalization; (3) Coping and Conformity (Religion as Support, Fitting In, Internalization); (4) Education and Understanding; and (5) Bystander Behavior (Experiences of Intervention, Religious Duty to Intervene, Consequences of Intervention). Findings highlight the extent to which racism occurs and the increased vulnerability of the Sikh community (e.g., appearance being the focus of racist abuse). Findings also highlight the importance of religion as a source of support and cultural pride and the significance of education and bystander behavior. Future research should further investigate these themes and introduce interventions to support the safety and well-being of members of the Sikh community experiencing racist abuse.